2017
DOI: 10.1016/j.meddos.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of peripheral NSCLC SBRT using Acuros XB and AAA calculation algorithms

Abstract: There is a concern for dose calculation in highly heterogenous environments such as the thorax region. This study compares the quality of treatment plans of peripheral non-small cell lung cancer (NSCLC) stereotactic body radiation therapy (SBRT) using 2 calculation algorithms, namely, Eclipse Anisotropic Analytical Algorithm (AAA) and Acuros External Beam (AXB), for 3-dimensional conformal radiation therapy (3DCRT) and volumetric-modulated arc therapy (VMAT). Four-dimensional computed tomography (4DCT) data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 14 publications
4
26
3
Order By: Relevance
“…Regarding PTV coverage parameters, our results differed from those published in the literature. While we found a lower D 95 and no significant difference in D 98 when comparing AAA with AXB, it is widely reported that AAA overestimates these parameters and the minimum dose 7,9,[18][19][20][21][22][25][26][27]30 . The reason for this discrepancy is that while our plans were initially optimized for AXB and then recalculated, keeping identical beam parameters for AAA, most prior studies adopted the opposite method.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…Regarding PTV coverage parameters, our results differed from those published in the literature. While we found a lower D 95 and no significant difference in D 98 when comparing AAA with AXB, it is widely reported that AAA overestimates these parameters and the minimum dose 7,9,[18][19][20][21][22][25][26][27]30 . The reason for this discrepancy is that while our plans were initially optimized for AXB and then recalculated, keeping identical beam parameters for AAA, most prior studies adopted the opposite method.…”
Section: Discussioncontrasting
confidence: 75%
“…An important aspect of our study concerns the change introduced with AXB v11 regarding the determination of tissue types from CT images 32,33 . The version of AXB used in our study could produce different results than those previously obtained in studies that used v10 [7][8][9]21,25,26,30 .…”
Section: Treatment Planning and Dose Calculationcontrasting
confidence: 75%
See 3 more Smart Citations